Implementation of Community-Based Citizenship Education to Improve the Civic Skills of the Young Generation in the Qarriyah Tayyibah Community, Kalibening Village, Tingkir District, Salatiga City - Lestiyawati, Eko; Nuryadi, Muh. Hendri; Winarno, Winarno (Pelopor Publikasi Akademika, 2024)
Citizenship education programs need to be developed to develop citizens in the community. One of them is community-oriented citizenship education, which is education that is designed, implemented, developed and assessed by the community which is aimed at responding to the challenges and opportunities that exist in a future-oriented community environment. This research describes the implementation of community-based citizenship education to improve the civic skills of the younger generation in the Qarryah Tayyibah Community, Kalibening Village, Tingkir District, Salatiga City. This research used a sample of 70 students from the Qarryah Tayyibah Community. This research used a qualitative research method with a purposive sampling technique. Data was taken using interviews, observation and questionnaires. The results of the research show that the implementation of community-based citizenship education can improve civic skills by using appropriate learning strategies according to students' learning materials. Policy recommendations that can be given are as follows, 1) Companions need to be provided with skills training, be it Technical Skills Training, Product Quality Training, Hard Skills Training, Soft Skills Training, Skills Training. 2) The government supports the curriculum according to the needs and interests of students. at the present time.